Implementasi Membaca Al-Qur'an dalam Manajemen Halusinasi pada Pasien Skizofrenia di RSJD Surakarta - Astrid Indah Istiningrum; Wita Oktaviana; Suparmi Suparmi (Lembaga Pengembangan Kinerja Dosen, 2025)
Mental disorder is a condition where a person considers himself/herself to be isolated from his/her surroundings, fails in his/her business, cannot control his/her emotions, and makes a person feel threatened, disturbed, or uncomfortable so that he/she changes his/her behavior, one of which is marked by sensory perception disorders of hallucinations. This case study aims to determine the effect of hallucination management with the implementation of reading the Qur'an on patients with unspecified schizophrenia in the Srikandi ward of Dr. Arif Zainuddin Mental Hospital, Surakarta City.: The design of this scientific paper uses a case study design. The subjects used were 5 (five) subjects. Data analysis was carried out by looking at changes before and after being given Qur'an reading therapy. The results of the application showed that after the implementation of Qur'an reading therapy, there was a decrease in signs of hallucination symptoms. Qur'an reading therapy can help reduce signs of symptoms and manage hallucinations in patients with unspecified schizophrenia. It is expected that nurses can provide psychiatric nursing care to hallucinatory patients by implementing the activity of reading the Qur'an consistently or repeatedly while undergoing treatment in the hospital and when returning home.